INNOVATIVE APPROACHES TO THE ANALYSIS OF REGIONAL INVESTMENT PROJECTS - Davlyatshayev Akmal Ashurmamatovich (Modern American Journals, 2025)
This article discusses modern approaches to the analysis of investment projects at the regional level. The author draws attention to the peculiarities of investment activity at the regional level, which plays an important role in the socio-economic development of regions, contributes to structural changes in the economy and helps solve social problems. The article presents a classification of investment projects according to various criteria, which may vary in level, objectives, timing of implementation and results. The stages of project analysis are also described in detail, from a preliminary examination to a comprehensive effectiveness assessment. The study focuses on managing investment processes at the regional level, including minimizing risks, supporting investors, and accelerating the implementation of investment programs.
Keywords: Investments, investment projects, regional investment analysis, investment processes, economic development, investment decision-making, investment risks, investment efficiency, investment legislation of Uzbekistan, investment monitoring.